Pendidikan Politik Masyarakat Bagi Pemilih Menjelang Pemilu Serentak di Desa Bentangan Wonosari Klaten Tahun 2024 - Nurhidayati, Indah; Prasetya Aditama, Yoga; Hasanah , Miftakhul; Ridwan Hidayat, Muhammad; Sukemi, Rochmawati Sholikah (LP3M IAIFA Kediri, 2024)
This community service aims to provide insight into knowledge to the community, especially to novice voters about political education ahead of the 2024 simultaneous election Democracy party. The target of the service is the novice voters and the people of the stretch village. Activities in the political education seminar with the theme of community Political Education for voters ahead of the simultaneous election in the village of Bentangan Wonosari Klaten in 2024 were held on Sunday 04 February 2024 at The Village Hall of Bentangan.The results of the service activities provide an overview that: political education seminars can increase the knowledge and insight of novice voters for simultaneous elections on February 14, 2024; The public is aware of the importance of the people's decommissioning party on February 14, but the public also does not all understand the candidates from the DPR RI, provincial DPRD, District DPRD and DPD; the need for innovation in the form of political education so as not to be judged by the campaign.